Malaysian consumers’ preferences in purchasing pineapples: a case study in Jasin, Melaka / Muhammad Amirul Shafik Bansan - Bansan, Muhammad Amirul Shafik (Faculty of Plantation and Agrotechnology, 2019)
Pineapples or Ananas Comosus from the family Bromeliaciae was a plant in which tropically origin from east Area of South America. Pineapple was started worldwide production by 15th century. Malaysia was well known as one of the world pineapple suppliers. Malaysia was the 18th top production pineapple in the world and the production of pineapple about 391714 a year. The objectives of this study was to determine the factors of Malaysian’s consumers’ preference in purchasing pineapples. From the factors, this study was to evaluate the most dominant factor of Malaysian’s consumers’ preferences in purchasing pineapples. A total of 200 respondents from Jasin, Melaka with objectives of identifying factors affecting Malaysian’s consumer’s preferences purchasing pineapple in the study area. Respondent were asked about demand toward pineapples, knowledge level on pineapples, characteristic of pineapples and consumer preferences purchasing pineapples. The obtained data were analysed using descriptive analysis and exploratory factor analysis. From the result KMO, 0.721 was reliable acceptable for conducting factor analysis since it was greater than 0.5. From factor analysis, the result illustrated that, the demand was the most dominant attribute towards Malaysian’s consumers’ preferences in purchasing pineapples. It was represented by three main factors which eigenvalues more than 1, consumer demand (3.942), consumer knowledge (2.602) and characteristic of pineapples (2.092). It was about 57.6 % of total variance were explained by three factors. From this result, it was proven that the consumer demand indirectly can increase pineapples production.